Atorvastatin-loaded emulsomes foam as a topical antifungal formulation - Alaa S. Eita; Amna M.A. Makky; Asem Anter; Islam A. Khalil (Elsevier, 2022)
Dermal fungal infection faces many challenges, especially for immunocompromised patients. Recently, the repositioning of atorvastatin (ATO) as a promising anti-mycoses therapy is used to overcome some issues of conventional therapeutic agents such as microbial resistance. The goal of this study was to develop a suitable formula for dermal fungal infection. Wherefore, ATO was entrapped into emulsomes and then incorporated in a foam system for topical convenient application. The D-optimal design was used for the optimization of ATO-emulsome and foam to achieve suitable responses. Regarding emulsomes, cholesterol weight and sonication time were independent variables that impact emulsome size, polydispersity index, surface charge, and entrapment efficiency. The optimum formula showed a size of 359.4 ± 8.97 nm, PDI of 0.4752 ± 0.012, a zeta potential of −21.27 ± 0.53 mV, and a drug entrapment of 95 ± 2.38%. Transmission electron microscope and Fourier-transform infrared spectroscopy (FT-IR) proved the assembly of ATO-emulsome. Foam composition was optimized to achieve good expansion, stability, and viscosity using a surfactant triple mixture and hydroxypropyl methylcellulose. The selected ATO-emulsome foam which consisted of 1% HPMC, 1.249% SDS, and 4% pluronic showed prolonged drug release. Efficient permeation through skin layers was asserted by using a confocal laser scanning microscope. Moreover, the homogenous distribution of the foam bubbles upholds stability and conserves the system from rapid collapse. The antifungal activity was confirmed by an in-vitro and in-vivo microbiology study beside in-vivo biocompatibility. In conclusion, ATO-emulsome and incorporation in foam have demonstrated good antifungal activity which presented a unique aspect for potential clinical applications.